PENGARUH MODERNISASI TERHADAP IDENTITAS BUDAYA MASYARAKAT DESA MOJODESO - Muhammad Fariz Laksono; Pambudi Handoyo (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This research explores the impact of modernization on the cultural identity of rural communities by focusing on a case study in Mojodeso Village. Research reveals the significance of changes in cultural values, daily life patterns, and social structures that are clearly visible in the context of strong modernization. The shift from traditional values towards individuality and economic aspects presents deep questions about how to maintain the continuity of old values while responding to changing times. Adaptation to modern life and technology is reflected in changes in consumption patterns, communication and work arrangements in Mojodeso. In addition, changes were observed in social structures and community characteristics, including intergenerational dynamics, marriage patterns, and gender roles. Even though there have been significant changes, traditional cultural values are still maintained. Customs, mutual cooperation activities and local wisdom in agriculture and the environment are maintained. The continuity of these values shows the cultural resilience of the Mojodeso people in facing the current of modernization. Analysis using Talcott Parsons' modernization theory provides deep insight into the role of modernization in changing cultural identity in rural areas. The implications for rural development emphasize the need to maintain traditional values while adapting to changing times. It is hoped that this research will contribute to policies that are wiser and more responsive to the cultural diversity and local identity of rural communities in the midst of ever-growing modernization.